The Skin Epilipidome in Stress, Aging, and Inflammation - Gruber, Florian; Marchetti-Deschmann, Martina; Kremslehner, Christopher; Schosserer, Markus (Frontiers in Endocrinology, 2021)
Lipids are highly diverse biomolecules crucial for the formation and function of cellular membranes, for metabolism, and for cellular signaling. In the mammalian skin, lipids additionally serve for the formation of the epidermal barrier and as surface lipids, together regulating permeability, physical properties, acidification and the antimicrobial defense. Recent advances in accuracy and specificity of mass spectrometry have allowed studying enzymatic and non-enzymatic modifications of lipids – the epilipidome- , multiplying the known diversity of molecules in this class. As the skin is an organ that is frequently exposed to oxidative-, chemical- and thermal stress, and to injury and inflammation, it is an ideal organ to study epilipidome dynamics, their causes and their biological consequences. Recent studies uncover loss or gain in biological function resulting from either specific modifications or the sum of the modifications of lipids. These studies suggest an important role for the epilipidome in stress responses and immune regulation in the skin. In this minireview we provide a short survey of the recent developments on causes and consequences of epilipidomic changes in the skin or in cell types that reside in the skin.